Isokinetic muscle performance in male professional handball players - Kaczmarek, P.; Lubiatowski, P.; Cisowski, P.; Dudzinski, W.; Grygorowicz, M.; Dzianach, M.; Romanowski, L. (British Journal of Sports Medicine, 2014)
Background: Muscle strength and endurance of the shoulder rotators is important for overhead throwing performance and dynamic glenohumeral stability. Isokinetic assessment of shoulder internal and external rotators is commonly used by clinicians to assess muscle performance. Objective: To evaluate the external (ER) and internal rotator (IR) muscles isokinetic peak torque, total work and strength ratios in handball players.Design Prospective study with control group and descriptive analysis.Setting Elite division handball players.Participants The pilot studies included 48 professional handball players of average age 24.0 (±4.5 years), height 187.1 (±5.9) and weight 9.0 (±11.6). Interventions: Isokinetic tests were performed concentrically at 180 and 270 deg/s using Biodex System 3 PRO in standard sitting position.Main outcome measurements Isokinetic peak torque, total work and strength ratios. Results: The differences between the athletes and controls regarding the peak torque at 180 deg/s and total work at 270 deg/s of the ER and IR muscles for dominant and non dominant shoulder were statistically significant. The control group presented higher ratios (D 85.8±26.9; ND 82.8±23.4) than handball players (D 65.4±13.3; ND 63.0±16.0)-differences were statistically significant. There were statistical differences between dominant and non dominant shoulder in both group for total work of the ER muscles. There were no statistical differences between dominant and non dominant shoulder in both group for peak torque of the ER and IR muscles. Conclusions: Handball players present higher isokinetic parameters comparing to normal population. The study establishes additional normative data on ER and IR muscle torque and total work on high-level male handball players.